Análise do ciclo de vida e de custo de pilar com diferentes traços de concreto frente a carbonatação: do berço ao túmulo - Lamberti, Lucas Alves (2015)
The concrete is the principal featured in the construction industry, in terms of volume and demand of natural resources for its production. It is need to seek sustainability through researches to assist in the upgrade industry. Studies for this purpose have been gaining ground in different areas, and exploring important information to human knowledge. Besides the environmental assessment, it is interesting to apply economic aspects. This research seeks to assess the sustainability of structural concrete by durability testing of carbonation in the laboratory and analyzing the modular Life Cycle Assessment (LCA - m) through the computer program SimaPro and Life Cycle Costs Analysis (LCCA). Evaluated the sustainability assessment of a reinforced concrete pillar of a standard building in Santa Maria region, RS - Brazil, ranging from the cement type (CPII - Z, CPIV and CPV-ARI) and characteristic strength levels (fck 30 and 50 MPa), since the phases of production, use, maintenance and deconstruction/recycling of this functional unit (period between cradle-togate). It is useful life was estimate by the analysis of carbonation coefficients, by natural and accelerated methods. It was conclude that the increase in concrete strength from 30 to 50 MPa is favorable in all the studied factors. The cement variation was decisive for fck = 30 MPa, for the life of the project for minimum standard was not met with CPIV and CPV-ARI. The cement CPII-Z achieved the best results.